Pelatihan Dan Penerapan Perpustakaan Digital di SMA N 1 Metro Kibang - Ahmad Ari Aldino; Very Hendra Saputra; Dedi Darwis (Journal of Engineering and Information Technology for Community Service, 2023)
The library is one of the means of library materials that has a function as a source of information to support the learning process in schools. The use of digital libraries can facilitate services in accessing needed learning resources, besides that with a digital library the process of borrowing and returning books will be easier to monitor by the library manager. The Indonesian Technocrat University PKM Team carried out a service program at the request of the management of SMA N 1 Metro Kibang in the form of training and application of a digital library, this was because the management of SMA N 1 Metro Kibang needed access to library digitization to facilitate the library management process, both in terms of borrowing, returning and monitoring the number of learning resources available in the library of SMA N 1 Metro Kibang. This introduction and training activity were attended by librarians, teachers and students of SMA N 1 Metro Kibang. The material provided in this activity is training in the form of a basic understanding of digital libraries, features in digital library applications, data processing which includes searching, borrowing and returning books, as well as reports on data on each book's borrowing which is recapitulated every month